Aleatorism and Sporting Performance - Kosiewicz Jerzy (Sciendo, 2017)
A sporting spectacle is an important cultural event, essentially influencing social and individual lives. In spite of this, there does not yet exist a monograph that analyzes, describes, and explains sporting performance from the point of view of aleatorism as part of the theory of sport and physical culture. Unfortunately, no monograph has developed this issue in a multi-aspectual, holistic, culturological, and philosophical way, dealing with its axiological values (aesthetic and praxeological). This applies to the relations between this phenomenon and the mechanisms that bring about the development and growth of interest in the social dimension.